Carbon dioxide reduction catalyst containing heterogeneous metals and its manufacturing method

KR103020138B1Active Publication Date: 2026-09-16DAEGU GYEONGBUK INSTITUTE OF SCIENCE AND TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
KR1020240004639
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Priority Date
2023-10-05
Filing Date
2024-01-11
Publication Date
2026-09-16
Estimated Expiration
2044-01-11

Smart Images

  • Figure 112024003964608-PAT00003_ABST
    Figure 112024003964608-PAT00003_ABST
Patent Text Reader

Abstract

The present invention relates to a carbon dioxide reduction catalyst and a method for manufacturing the same, comprising: copper oxide particles having a polyhedral structure; and second silver (Ag) particles located on the surface of the copper oxide particles, wherein a plurality of first silver (Ag) particles are aggregated. By controlling the microstructure of the catalyst surface, the selectivity for C2+ compounds having two or more carbon atoms, particularly ethylene, can be significantly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to a carbon dioxide reduction catalyst comprising heterogeneous metals and a method for manufacturing the same. Background Technology

[0002] The electrochemical carbon dioxide conversion reaction is attracting attention as a next-generation energy technology because it consumes carbon dioxide, one of the greenhouse gases that cause global warming, and converts it into compounds with high industrial value.

[0003] Various metal catalysts are used as catalysts for carbon dioxide conversion reactions. Among these metals, copper (Cu) has the advantage of being highly useful as a carbon dioxide conversion catalyst because it can produce not only C1 compounds such as carbon monoxide (CO) and formic acid (HCOOH) but also high-value C2 compounds such as ethylene (C2H4), ethanol (CH3CH2OH), and acetic acid (CH3COOH). However, due to these characteristics, conventional copper catalysts have a problem of low selectivity for specific products, particularly C2 compounds.

[0004] To address these issues, strategies are being pursued to improve selectivity for specific products by controlling reaction intermediates during carbon dioxide conversion through catalyst design modifications, such as altering the catalyst structure. However, due to the complex reaction pathway of the carbon dioxide conversion reaction, there are still limitations in improving selectivity for compounds with two or more carbon atoms, such as ethylene. In particular, since the carbon dioxide conversion reaction takes place on the surface of the catalyst, understanding the surface structure of the catalyst to control the binding energy of reaction intermediates remains a critical task in order to obtain the desired product from carbon dioxide. The problem to be solved

[0005] The object of the present invention is to solve the problem of the prior art described above, wherein C having 2 or more carbon atoms 2+ The purpose is to provide a carbon dioxide conversion catalyst that improves the selectivity for compounds, specifically ethylene. means of solving the problem

[0006] The carbon dioxide reduction catalyst according to the present invention comprises: copper oxide particles having a polyhedral structure; and second silver (Ag) particles located on the surface of the copper oxide particles, wherein a plurality of first silver (Ag) particles are aggregated.

[0007] In one example, the second silver (Ag) particle may be located on the (100) plane of the copper oxide particle.

[0008] In one example, the ratio (D1 / D2) of the average particle size (D1) of the first silver (Ag) particle and the average particle size (D2) of the second silver (Ag) particle may be 0.01 to 0.5.

[0009] In one example, the copper oxide particles may have a hexahedral structure.

[0010] In one example, the catalyst may be used for the production of ethylene.

[0011] In one example, the size of the copper oxide particles may be 500 to 1000 nm.

[0012] In one example, the copper oxide particles may contain Cu2O.

[0013] The present invention includes a method for manufacturing the carbon dioxide reduction catalyst described above.

[0014] A method for manufacturing a carbon dioxide reduction catalyst according to the present invention comprises: (S1) a step of producing copper oxide particles with a polyhedral structure by adding a reducing agent to a solution containing a copper precursor; and (S2) a step of adding a silver (Ag) precursor to the solution containing the copper oxide particles.

[0015] In one example, the copper precursor-containing solution may further include polyvinylpyrrolidone (PVP).

[0016] In one example, the molar ratio of the polyvinylpyrrolidone (PVP) and the copper precursor may be 5 to 50:1.

[0017] In one example, the above step (S2) may be a galvanic replacement reaction between a silver (Ag) precursor and copper oxide on the surface of copper oxide particles.

[0018] A carbon dioxide conversion method according to the present invention comprises the steps of: supplying carbon dioxide to a reactor comprising the carbon dioxide reduction catalyst described above; and discharging a product generated by reducing the carbon dioxide.

[0019] In one example, among the above products, a compound having 2 or more carbon atoms (C 2+ The ratio of ) and the Faraday efficiency of a compound with 1 carbon atom (C1) (C 2+ / C1) can be 1.5 to 4.0.

[0020] In one example, the product gas may include ethylene. Effects of the invention

[0021] The carbon dioxide conversion catalyst of the present invention is C having 2 or more carbon atoms. 2+ The selectivity for compounds, specifically ethylene, can be improved. Brief explanation of the drawing

[0022] FIG. 1 is (a) SEM images, STEM-EDS mapping images, and HRTEM images of catalysts prepared by the methods of Comparative Examples 3 to 5 before and after the carbon dioxide reduction reaction, (c) XRD spectra of catalysts before and after the carbon dioxide conversion reaction, and (d) EXAFS (Extended X-ray absorption fine structure) spectra of the catalyst according to Comparative Example 3 after the carbon dioxide conversion reaction, Fourier transformed in the Cu k-edge range 0 to 7. FIG. 2 is (a) SEM image, STEM-EDS mapping image, and HRTEM image of the catalyst prepared by the methods of Comparative Examples 6 to 8 before and after the carbon dioxide reduction reaction, (c) XRD spectrum of the catalyst before and after the carbon dioxide conversion reaction, and (d) EXAFS (Extended X-ray absorption fine structure) spectrum of the catalyst according to Comparative Example 6 after the carbon dioxide conversion reaction, in the Cu k-edge range 0 to 7, which is Fourier transformed. FIG. 3 is (a) SEM images, STEM-EDS mapping images, and HRTEM images of catalysts prepared by the methods of Example 1, Comparative Example 1, and Comparative Example 2 before and after the carbon dioxide reduction reaction, (c) XRD spectra of catalysts before and after the carbon dioxide conversion reaction, and (d) EXAFS (Extended X-ray absorption fine structure) spectra of the catalyst according to Example 1 in the Cu k-edge range 0 to 7 after the carbon dioxide conversion reaction. FIGS. 4(a) to (c) are Comparative Examples 3 to 5, FIGS. 4(d) to (f) are Comparative Examples 6 to 8, FIGS. 4(g) to (i) are drawings showing the product selectivity when the carbon dioxide reduction catalysts of Example 1, Comparative Example 1, and Comparative Example 2 are subjected to a carbon dioxide conversion reaction using the method of Experimental Example 1. FIGS. 5(a) to (c) show 200 to 700 cm of the catalyst according to Comparative Example 3, Comparative Example 6, and Example 1, respectively. -1 Raman spectra at, and FIGS. 5(d) to (f) are the 1800 to 2300 cm⁻¹ spectra of the catalysts according to Comparative Example 3, Comparative Example 6, and Example 1, respectively. -1This is the Raman spectrum at, FIG. 5(g) is a graph showing the calculated HFB / (LFB+HFB) values ​​of the catalysts according to Example 1, Comparative Example 3, and Comparative Example 6, and FIG. 5(h) shows that in the catalysts of Example 1, Comparative Example 3, and Comparative Example 6, C 2+ Ratio of Faraday efficiency of compounds and C1 compounds (C 2+ This is a graph measuring / C1). Specific details for implementing the invention

[0023] The carbon dioxide reduction catalyst comprising heterogeneous metals according to the present invention and the method for manufacturing the same are described in detail. The terms used in this specification have been selected to be as widely used as possible while considering the functions of the present invention; however, these may vary depending on the intent of those skilled in the relevant field, case law, the emergence of new technologies, etc. Unless otherwise defined, technical and scientific terms used may have the meaning commonly understood by those skilled in the art to which this invention pertains.

[0024] In this specification and the appended claims, terms such as “comprising” or “having” mean that the features or components described in the specification exist, and unless specifically limited, do not preclude the possibility that one or more other features or components may be added.

[0025] In this specification and the appended claims, terms such as "first," "second," etc. are used not in a limiting sense, but for the purpose of distinguishing one component from another.

[0026] Singular expressions used in this specification and the appended claims include plural expressions unless the context clearly indicates that they are singular. Additionally, plural expressions include singular expressions unless the context clearly indicates that they are plural.

[0027] Additionally, the numerical ranges used in this specification include lower and upper limits and all values ​​within the range, increments logically derived from the form and width of the defined range, all of which are limited values, and all possible combinations of upper and lower limits of numerical ranges defined in different forms. Unless otherwise specifically defined in this specification, values ​​outside the numerical range that may occur due to experimental error or rounding are also included in the defined numerical range.

[0028] Terms such as "approximately" used in this specification and the appended claims are used to encompass tolerances when tolerances exist.

[0029] In this specification, “selectivity” refers to the Faraday efficiency, which represents the ratio of the amount of charge used to produce the product to the total amount of charge during the electrochemical conversion of carbon dioxide.

[0030] The electrochemical carbon dioxide conversion reaction is attracting attention as a next-generation energy technology because it consumes carbon dioxide, one of the greenhouse gases that cause global warming, and converts it into compounds with high industrial value.

[0031] Various metal catalysts are used as catalysts for carbon dioxide conversion reactions; among these metals, copper (Cu) is used not only for C1 compounds such as carbon monoxide (CO) and formic acid (HCOOH) but also for high-value compounds such as ethylene (C2H4), ethanol (CH3CH2OH), and acetic acid (CH3COOH). 2+ It has the advantage of being highly useful as a carbon dioxide conversion catalyst because it can produce compounds. However, due to this characteristic, conventional copper catalysts have a problem of low selectivity for specific products, particularly multi-carbon compounds with two or more carbon atoms.

[0032] To address these issues, strategies are being pursued to improve selectivity for specific products by controlling reaction intermediates during carbon dioxide conversion through catalyst design modifications, such as altering the catalyst structure or adding metals different from copper. However, C with two or more carbon atoms, such as ethylene, is still... 2+ There are limitations to improving the selectivity for compounds.

[0033] Accordingly, after in-depth research, the applicant, by controlling the interface arrangement and shape between heterogeneous metal particles, C resulting from the synergistic effect between the metal particles 2+ We have developed a carbon dioxide reduction catalyst capable of improving the selectivity of compounds.

[0034] The carbon dioxide reduction catalyst of the present invention comprises: copper oxide particles having a polyhedral structure; and second silver (Ag) particles located on the surface of the copper oxide particles, wherein a plurality of first silver (Ag) particles are aggregated.

[0035] Through silver(Ag) particles existing in an aggregated form on the surface of copper oxide particles, C with 2 or more carbon atoms 2+ The selectivity for the compound can be improved. Specifically, carbon dioxide is converted into carbon monoxide through aggregated silver(Ag) particles, and subsequently, a large amount of carbon monoxide intermediate can be adsorbed onto the surface of copper oxide particles. By promoting the dimerization of carbon monoxide intermediate on the surface of copper oxide particles, a large amount of C 2+ Compounds can be formed. Since silver (Ag) particles exist in an aggregated state on the surface of copper oxide particles, not only silver (Ag) but also copper (Cu) is exposed on the catalyst surface, which can increase the contact area with the reactants. Accordingly, the binding energy barrier of the carbon monoxide intermediate is lowered, allowing for more efficient C 2+ Selectivity and productivity for compounds can be improved.

[0036] The second silver (Ag) particle can be located on the (100) plane of the copper oxide particle. A plurality of first silver (Ag) particles can easily aggregate on the (100) plane having low surface energy to form the second silver (Ag) particle.

[0037] A catalyst containing aggregated silver (Ag) particles, rather than small silver (Ag) particles dispersed on the surface of copper oxide particles, controls the microenvironment of the reduction intermediate during the carbon dioxide reduction reaction and lowers the binding energy of the intermediate, thereby C 2+ It is possible to create an environment optimized for forming compounds.

[0038] In one embodiment, the ratio (D1 / D2) of the average particle size (D1) of the first silver (Ag) particle and the average particle size (D2) of the second silver (Ag) particle may be 0.01 to 0.5, 0.015 to 0.4, or 0.02 to 0.3. Within the above particle size range, the catalyst has a high specific surface area and at the same time C 2+ Selectivity for compounds can be improved.

[0039] In one example, the copper oxide particles may have a hexahedron, cuboctahedron, or octahedron structure having a size of 500 to 1000 nm, 550 to 900 nm, or 600 to 800 nm, and preferably, the copper oxide particles may have a hexahedron structure.

[0040] Octahedrons and cuboctahedrons containing (111) faces with high surface energy find it difficult to form aggregated structures as first silver (Ag) particles introduced onto the surface of copper oxide particles disperse rapidly, whereas when copper oxide particles have a cubic structure, the first silver (Ag) particles aggregate to easily form second silver (Ag) particles, and by controlling the distance between the silver (Ag) particles and copper particles, reaction intermediates generated on the surface of the silver (Ag) particles are moved to the surface of the copper particles, thus C 2+ Selectivity for compounds can be improved.

[0041] In one example, the copper oxide particles may contain copper having an oxidation number of 1, and more specifically, the copper oxide particles may contain Cu2O. Copper oxide having an oxidation number of 1 is obtained from carbon dioxide C 2+ It has the advantage of being favorable for forming compounds.

[0042] In one example, the carbon dioxide reduction catalyst is a C having 2 or more carbon atoms. 2+ It may be a catalyst for the production of compounds, and more specifically, a catalyst for the production of ethylene. As described above, the selectivity for ethylene can be significantly improved through the dimerization of carbon monoxide intermediates as carbon monoxide intermediates generated through aggregated silver (Ag) particles migrate to the surface of copper particles. In particular, ethylene can be produced from carbon dioxide more efficiently by lowering the bond energy required for the dimerization of carbon monoxide intermediates.

[0043] The present invention includes a method for manufacturing a carbon dioxide reduction catalyst as described above. In describing the method for manufacturing a carbon dioxide reduction catalyst, the material, structure, shape, or size of the copper oxide particles, the first silver (Ag) particles, and the second silver (Ag) particles are identical or similar to those described above; therefore, the method for manufacturing a carbon dioxide reduction catalyst according to the present invention includes all the details described above.

[0044] A method for manufacturing a carbon dioxide reduction catalyst according to the present invention comprises: (S1) a step of producing copper oxide particles with a polyhedral structure by adding a reducing agent to a solution containing a copper precursor; and (S2) a step of adding a silver (Ag) precursor to the solution containing the copper oxide particles.

[0045] (S1) Step of forming copper oxide particles with a polyhedral structure by adding a reducing agent to a solution containing a copper precursor solution, wherein the reducing agent may include one or more selected from the group including, for example, hydrazine (N2H4), NaBH4, LiAlH4, ascorbic acid, oxalic acid, and formic acid, and more specifically may include ascorbic acid, but the present invention is not limited thereto.

[0046] The copper precursor may include one or more hydrates selected from the group comprising copper sulfate, copper nitrate, copper carbonate, copper acetate, and copper chloride, and more specifically, may include copper chloride hydrate, but the present invention is not limited thereto.

[0047] In one example, the copper precursor-containing solution may further include polyvinylpyrrolidone (PVP). As the carbonyl group of polyvinylpyrrolidone is selectively attached to the (111) surface of the partially positively charged copper oxide particles, the shape of the copper oxide particles produced can be controlled by controlling the content of polyvinylpyrrolidone.

[0048] For example, when the copper precursor-containing solution further contains polyvinylpyrrolidone, the molar ratio of polyvinylpyrrolidone (PVP) to the copper precursor may be 5 to 50:1, 9 to 42:1, or 13 to 36:1. When polyvinylpyrrolidone is contained in the above molar ratio, the structure of the copper oxide particles can be controlled.

[0049] Step (S2) is a step of introducing a silver (Ag) precursor into a solution containing copper oxide particles with a polyhedral structure manufactured through Step (S1), which can produce second silver (Ag) particles in which first silver (Ag) particles are aggregated on the surface of copper oxide particles.

[0050] For example, in step (S2), a galvanic replacement reaction between silver (Ag) and copper oxide can be performed on the surface of the copper oxide particles. Silver (Ag), which is more reducing than copper, can spontaneously proceed with the reaction on the surface of the copper oxide particles. Specifically, the galvanic replacement reaction may involve the following reaction scheme 1.

[0051] [Reaction Equation 1]

[0052] 2H + + Cu2O + 2Ag + → 2Ag + H2O + 2Cu 2+

[0053] At this time, since the (100) crystal plane of the copper oxide particle has low surface energy, the silver (Ag) particle prefers aggregation among silver (Ag) particles rather than galvanic substitution reaction with copper, so aggregation of silver (Ag) particles may occur on the surface of the copper oxide particle.

[0054] In one embodiment, the silver precursor may include silver nitrate (AgNO3), silver sulfate (Ag2SO4), silver acetate (AgC2H3O2), silver chloride (AgCl), silver oxide (Ag2O), or a combination thereof, and preferably may include silver nitrate, but the present invention is not limited thereto.

[0055] The present invention includes a method for converting carbon dioxide using the aforementioned carbon dioxide reduction catalyst. Since the carbon dioxide reduction catalyst is the same as described above, a detailed description is omitted.

[0056] A carbon dioxide conversion method according to the present invention comprises: a step of supplying carbon dioxide to a reactor comprising the aforementioned carbon dioxide reduction catalyst; and a step of discharging a product generated by reducing the carbon dioxide.

[0057] As described above, in the carbon dioxide reduction catalyst of the present invention, since agglomerated silver (Ag) particles are located on the surface of polyhedral copper oxide particles, the surface area where copper (Cu) comes into contact with carbon dioxide and reaction intermediates can be increased. Accordingly, carbon dioxide forms carbon monoxide intermediates on the surface of the agglomerated silver (Ag) particles, and the carbon monoxide intermediates can be easily adsorbed onto the surface of the copper oxide particles. The copper oxide particles promote the dimerization of carbon monoxide intermediates, thereby [removing] C with two or more carbon atoms 2+ Compounds can be manufactured with high selectivity.

[0058] For example, among the above products, a compound having 2 or more carbon atoms (C 2+ The ratio of ) and the Faraday efficiency of a compound with 1 carbon atom (C1) (C 2+ / C1) is 1.5 to 4.0, 2.0 to 3.5, or 2.3 to 3.0, relative to a C1 compound having 1 carbon atom, C having 2 or more carbon atoms. 2+ It can have significant selectivity for compounds.

[0059] The above C 2+Examples of compounds include ethylene (C2H4), ethanol (CH3CH2OH), acetic acid (CH3COOH), and propylene (C3H6). More specifically, when using the carbon dioxide reduction catalyst of the present invention, the effect of improving selectivity for ethylene (C2H4) can be maximized.

[0060] In one embodiment, the reactor may include one of a batch, semi-continuous, or continuous type, but it is advantageous to use a continuous flow reactor that can improve reaction efficiency by continuously supplying reactants.

[0061] The reactor may include a first electrode comprising the carbon dioxide conversion catalyst described above, a second electrode disposed opposite the first electrode, and an electrolyte in contact with the first and second electrodes. More specifically, the first electrode may include a porous support on which the catalyst is immobilized, and even more specifically, the porous support may be a gas diffusion layer (GDE). A gas diffusion layer is advantageous because it can improve reaction activity and increase productivity by directly supplying reactants to the surface of the catalyst.

[0062] The porous support may adopt a porous material containing micropores, and advantageously may include a carbon-based material having conductivity. More specifically, the carbon-based material may include one or more selected from the group comprising glassy carbon, carbon black, carbon paper, carbon nanotubes, and graphene. In addition, the average pore diameter of the porous support may be 1 to 500 nm or 5 to 300 nm, and preferably 10 to 100 nm, but the present invention is not limited by the pore size and type of the porous support.

[0063] The electrolyte may include an aqueous solution of sodium chloride (NaCl), potassium chloride (KCl), sodium hydroxide (NaOH), potassium bicarbonate (KHCO3), or potassium hydroxide (KOH), but the present invention is not limited by the specific type of electrolyte.

[0064] As a non-limiting example, the second electrode may use one or more metals selected from the group including nickel (Ni), gold (Au), silver (Ag), titanium (Ti), copper (Cu), platinum (Pt), and stainless steel, but the present invention is not limited thereto.

[0065] Additionally, the reactor may further include a separator that selectively permeates ions. Specifically, the separator may be an anion exchange membrane (AEM) that has excellent durability, low gas permeability, and high ion conductivity. Such anion exchange membrane may include porous thin films based on ion exchange resins and ionomers known in the art, and examples include Nafion™ of DuPont, Aquivion of Solvey, and Fumasep ion exchange membranes of Fumatek, but the present invention is not limited thereto.

[0066] The present invention will be explained in more detail below through examples.

[0067] (Example 1) Preparation of Ag / Cu2O cube

[0068] A 100 mL aqueous solution containing 0.01 Mol / L of CuCl2*2H2O was prepared as a copper precursor solution. 10 mL of a 2.0 M NaOH aqueous solution was added dropwise to the copper precursor solution and stirred for 0.5 hours, then 10.0 mL of 0.6 M ascorbic acid was added dropwise, and the mixture was aged for 3 hours to prepare copper oxide particles with a cube structure.

[0069] An aqueous silver nitrate solution was added to the copper oxide particle-containing solution and stirred for 10 minutes. Afterward, a carbon dioxide reduction catalyst was obtained by centrifugation and drying. This was named Ag / Cu2O cube.

[0070] (Comparative Example 1) Preparation of Ag / Cu2O cubo

[0071] A carbon dioxide reduction catalyst was prepared in the same manner as in Example 1, except that polyvinylpyrrolidone (PVP) with a molecular weight of 40,000 was dissolved in a copper precursor solution at a molar ratio of PVP : CuCl2*2H2O = 13 : 1 to prepare copper oxide particles with a cuboctahedron structure. This was named Ag / Cu2O cubo.

[0072] (Comparative Example 2) Preparation of Ag / Cu2O octa

[0073] A carbon dioxide reduction catalyst was prepared in the same manner as in Example 1, except that copper oxide particles with an octahedron structure were prepared by mixing PVP with a molecular weight of 40,000 and CuCl2*2H2O in a molar ratio of 36:1 with a copper precursor solution. This was named Ag / Cu2O octa.

[0074] (Comparative Example 3) Preparation of bare Cu2O cube

[0075] A carbon dioxide conversion catalyst was prepared in the same manner as in Example 1, but without mixing the copper oxide particle-containing solution with an aqueous silver nitrate solution. Copper oxide particles were obtained by centrifuging and decanting the copper oxide particle-containing solution, then washed three times with distilled water and subsequently washed twice with anhydrous ethanol to remove residual inorganic ions and polymers. After the washing process, the particles were dried under vacuum for 5 hours to produce bare copper oxide particles with a cubic structure. These were named bare Cu2O cubes.

[0076] (Comparative Example 4) Preparation of bare Cu2O cubo

[0077] A carbon dioxide reduction catalyst was prepared in the same manner as in Comparative Example 3, except that copper oxide particles with a cuboctahedron structure were prepared by mixing PVP with a molecular weight of 40,000 and CuCl2*2H2O in a molar ratio of 13:1 in a copper precursor solution. This was named bare Cu2O cubo.

[0078] (Comparative Example 5) Preparation of bare Cu2O octa

[0079] A carbon dioxide reduction catalyst was prepared in the same manner as Comparative Example 3, except that copper oxide particles with an octahedron structure were prepared by mixing PVP with a molecular weight of 40,000 and CuCl2*2H2O in a molar ratio of 36:1 in a copper precursor solution. This was named bare Cu2O octa.

[0080] (Comparative Example 6) Preparation of Au / Cu2O cube

[0081] A carbon dioxide reduction catalyst was prepared in the same manner as in Example 1, except that an aqueous HAuCl4 solution was used instead of an aqueous silver nitrate solution in the copper oxide particle-containing solution. This was named Au / Cu2O cube.

[0082] (Comparative Example 7) Preparation of Au / Cu2O cubo

[0083] A carbon dioxide reduction catalyst was prepared in the same manner as in Comparative Example 1, except that an aqueous HAuCl4 solution was used instead of an aqueous silver nitrate solution in the copper oxide particle-containing solution. This was named Au / Cu2O cubo.

[0084] (Comparative Example 8) Preparation of Au / Cu2O octa

[0085] A carbon dioxide reduction catalyst was prepared in the same manner as in Comparative Example 2, except that an aqueous HAuCl4 solution was used instead of an aqueous silver nitrate solution in the copper oxide particle-containing solution. This was named Au / Cu2O octa.

[0086] (Experimental Example 1) Carbon Dioxide Conversion Reaction Experiment

[0087] A catalyst slurry was prepared by mixing 5 mg of carbon dioxide reduction catalyst with 0.5 ml of isopropanol and 10 µl of Nafion. A gas diffusion electrode was prepared by spraying the prepared catalyst slurry onto a gas diffusion layer (carbon paper, 39BB).

[0088] The electrochemical reduction reaction of carbon dioxide was performed using a flow reactor in which CO gas (50 mL / min) was continuously supplied. The gas diffusion electrode was set as the working electrode, Ni foam as the counter electrode, and Ag / AgCl (3 M KCl) as the reference electrode. 1 M KOH (pH 13.8) was used as the electrolyte, and an anion exchange membrane was used to separate the working electrode and the counter electrode.

[0089] The carbon dioxide reduction reaction was carried out for one hour. The gaseous products were collected in a gas-tight syringe (Hamilton, 1005SL) and injected three times into a gas chromatography system (YL6500 GC System) to analyze their composition, while the liquid products were analyzed using a nuclear magnetic resonance spectrometer (NMR, Bruker). Catholites were collected in NMR tubes containing a standard solution of a mixture of D2O and dimethyl sulfoxide. The Faraday efficiency (FE) for each product was calculated using Equation 1 below.

[0090] [Equation 1]

[0091] Faraday Efficiency (%) = (z·n·F) / Q

[0092] (Z and n are the number of electrons exchanged and the yield of the product (mol), respectively; F is the Faraday constant; and Q represents the input charge.)

[0093] The microstructure of the catalyst was observed using a field emission scanning electron microscope (FE-SEM, Hitachi / S-4800) and a super-resolution transmission electron microscope (TEM, Temis Z), and X-ray spectral analysis (XRD) was performed using a multipurpose X-ray diffractometer (Panalytic / Empyrean).

[0094] FIG. 1 is (a) SEM images, STEM-EDS mapping images, and HRTEM images of catalysts prepared by the methods of Comparative Examples 3 to 5 before and after the carbon dioxide reduction reaction, (c) XRD spectra of catalysts before and after the carbon dioxide conversion reaction, and (d) EXAFS (Extended X-ray absorption fine structure) spectra of the catalyst according to Comparative Example 1, Fourier transformed in the Cu k-edge range 0 to 7 after the carbon dioxide conversion reaction.

[0095] Referring to Fig. 1(a), during the catalyst preparation process, the carbonyl groups of polyvinylpyrrolidone interacted with the (111) plane of the partially positively charged copper oxide, so that polyvinylpyrrolidone was selectively attached to the (111) plane of the copper oxide particles. By controlling the content of polyvinylpyrrolidone mixed into the copper precursor solution, Cu2O particles with hexahedral, octahedral, or hexaoctahedral structures with uniform sizes ranging from 600 to 800 nm were prepared. In the XRD spectrum of Fig. 1(c), a narrow and strong peak for Cu2O (JCPDS 00-001-1142) was observed, indicating that the crystallinity of the catalyst is excellent. By controlling the molar ratio of polyvinylpyrrolidone to the copper precursor, the structure of the copper oxide particles could be varied.

[0096] Meanwhile, as shown in Fig. 1(b), the surface roughness of the catalyst increased after the carbon dioxide conversion reaction, and looking at the XRD spectrum in Fig. 1(d), the peak intensity for Cu (JCPDS 00-003-1005) increased due to the redeposition of copper ions on the surface of copper oxide particles during the electrochemical reduction reaction. Referring to Fig. 1(e), the peak intensity at 1.5 to 1.6 Å associated with Cu single-atom bonds during the carbon dioxide reduction reaction tended to decrease due to electrolysis, whereas the peak intensity of the Cu-Cu bond at 2.2 Å increased strongly. This is because copper ions formed by the reduction of copper oxide particles during the carbon dioxide reduction reaction aggregated to form Cu clusters.

[0097] FIG. 2 is (a) SEM image, STEM-EDS mapping image, and HRTEM image of the catalyst prepared by the methods of Comparative Examples 6 to 8 before and after the carbon dioxide reduction reaction, (c) XRD spectrum of the catalyst before and after the carbon dioxide conversion reaction, and (d) EXAFS (Extended X-ray absorption fine structure) spectrum of the catalyst according to Comparative Example 6 after the carbon dioxide conversion reaction, in the Cu k-edge range 0 to 7, which is Fourier transformed.

[0098] As shown in FIG. 2(a), a galvanic substitution reaction between copper (Cu) and gold (Au) occurred on the surface of the copper oxide particles, and the copper oxide particles effectively maintained their initial shape even after the introduction of gold (Au) particles. Specifically, in the catalyst of Comparative Example 6 (Au / Cu2O cube), gold (Au) particles existed in an aggregated form on the surface of the copper oxide particles. This is because gold (Au) particles prefer Au-Au aggregation over galvanic substitution with copper (Cu) on the (111) crystal plane of Cu2O, which has low surface energy. In the catalyst of Comparative Example 7 (Au / Cu2O cubo), gold (Au) particles were uniformly dispersed on the surface of the copper oxide particles, and in Comparative Example 8 (Au / Cu2O octa), both aggregated gold (Au) particles and dispersed gold (Au) particles were observed. Referring to FIG. 2(c), the XRD spectra of the catalysts of Comparative Examples 6 to 8 matched the crystal structures of Cu2O (JCPDS #00-001-1142) and Au (JCPDS 10-001-1172), and in particular, in Comparative Example 6 (Au / Cu2O cube), Au (111) and Au (200) peaks were observed at 38.269° and 44.6°, respectively, due to the presence of aggregated gold (Au) particles.

[0099] After performing the carbon dioxide reduction reaction using the method of Experimental Example 1, as shown in FIG. 2(b), it was confirmed that the surface roughness of the catalysts of Comparative Examples 6 to 8 increased, and that Au and Cu remained together, maintaining metallic properties. In the XRD spectrum of FIG. 2(d), it can also be confirmed that the peak for Au was preserved even after the carbon dioxide reduction reaction. Referring to FIG. 2(e), in the catalyst according to Comparative Example 6 (Au / Cu2O cube) during the carbon dioxide conversion reaction, most of the copper oxide (Cu2O) particles were reduced to Cu, and the Cu-Cu coordination number (CN) increased.

[0100] FIG. 3 is (a) SEM images, STEM-EDS mapping images, and HRTEM images of catalysts prepared by the methods of Example 1, Comparative Example 1, and Comparative Example 2 before and after the carbon dioxide reduction reaction, (c) XRD spectra of catalysts before and after the carbon dioxide conversion reaction, and (d) EXAFS (Extended X-ray absorption fine structure) spectra of the catalyst according to Example 1 in the Cu k-edge range 0 to 7 after the carbon dioxide conversion reaction.

[0101] Referring to FIG. 3(a), it was confirmed that galvanic substitution reactions between copper (Cu) and silver (Ag) also occurred on the surface of copper oxide particles in the catalysts of Example 1, Comparative Example 1, and Comparative Example 2. Specifically, in the catalyst of Example 1 (Ag / Cu2O cube), as previously described, silver (Ag) particles aggregated on the (100) crystal plane of Cu2O, which has low surface energy. On the other hand, in the case of Comparative Example 2 (Ag / Cu2O octa), where only the (111) crystal plane of the copper oxide particles exists, silver (Ag) particles were uniformly dispersed throughout the copper oxide particles. Unlike Comparative Example 8 (Au / Cu2O octa), in which aggregated gold particles and dispersed gold particles coexist, no aggregated silver (Ag) particles were observed in Comparative Example 2 (Ag / Cu2O octa). This is presumed to be because the surface energy of Ag is lower than that of Au on the (111) crystal plane of Cu2O, and thus the surface diffusion rate of Ag is faster. In the catalyst of Comparative Example 1 (Ag / Cu2O cubo), the galvanic substitution reaction tended to be more preferred on the (111) plane of Cu2O than on the (100) plane, and the silver (Ag) particles were uniformly dispersed, resulting in increased surface roughness. Looking at the XRD analysis spectrum in Fig. 3(c), the catalysts of Comparative Example 1 (Ag / Cu2O cubo) and Comparative Example 2 (Ag / Cu2O octa) had silver (Ag) particles highly dispersed on the surface of copper oxide particles, and because the size of the silver (Ag) particles was small, no peak for Ag was observed. However, in Example 1 (Ag / Cu2O cube), Ag (111) and Ag (200) peaks were observed at 38.115° and 44.299°, respectively, confirming that aggregation between Ag and Ag occurred.

[0102] After performing the carbon dioxide reduction reaction using the method of Experimental Example 1, the surface roughness of the catalyst increased as shown in Fig. 3(b), and metallic Ag was present. More specifically, in the XRD spectrum of Fig. 3(d), the catalyst of Example 1 (Ag / Cu2O cube) preserved the peak for Ag even after the carbon dioxide reduction reaction. For the catalysts of Comparative Example 1 (Ag / Cu2O cube) and Comparative Example 2 (Ag / Cu2O octa), the peak for the Ag (200) plane was weakly observed after the carbon dioxide reduction reaction, which is because the mobility of Ag is slower than that of Cu and Ag tends to aggregate during the reaction. In the case of Fig. 3(e), when the catalyst of Example 1 was used for the carbon dioxide conversion reaction, the copper oxide particles were completely reduced during the reaction, and a very strong peak for the Cu-Cu bond was detected at 1.5 to 3.0 Å, and the Cu-Cu coordination number increased.

[0103] FIGS. 4(a) to (c) are Comparative Examples 3 to 5, FIGS. 4(d) to (f) are Comparative Examples 6 to 8, FIGS. 4(g) to (i) are drawings showing the product selectivity when the carbon dioxide reduction catalysts of Example 1, Comparative Example 1, and Comparative Example 2 are used in the carbon dioxide conversion reaction according to the method of Experimental Example 1.

[0104] In the case of Comparative Examples 3 to 5, as shown in FIGS. 4(a) to (c), since only copper oxide particles were contained without secondary metals such as gold or silver, the Faraday efficiency for hydrogen was high at 20% or higher, and the Faraday efficiency for ethylene was low at about 10%. The bare copper oxide particles of Comparative Examples 3 to 5 not only failed to suppress the competing reaction, the hydrogen evolution reaction (HER), but also had very low selectivity for C2 compounds.

[0105] As shown in FIGS. 4(d) to (f), the Au / Cu2O catalysts of Comparative Examples 6 to 8 also failed to inhibit the hydrogen evolution reaction, as their Faraday efficiency for hydrogen was very high at 18% or higher, regardless of the structure of the copper oxide particles. Accordingly, the Faraday efficiency for ethylene was measured to be low at 20% or less, whereas the Faraday efficiency for carbon monoxide was high at 25 to 40%. Accordingly, C with 2 or more carbon atoms 2+ There were limitations in improving the selectivity for the compound.

[0106] On the other hand, in the case of Example 1 (Ag / Cu2O cube), referring to FIGS. 4(g) to (i), the Faraday efficiency for hydrogen was low at 10 to 20%, and the Faraday efficiency for ethylene (C2H4) was measured to be 30% or higher, effectively suppressing the competing hydrogen generation reaction while simultaneously improving selectivity for ethylene with 2 or more carbon atoms. The catalysts of Comparative Example 1 (Ag / Cu2O cube) and Comparative Example 2 (Ag / Cu2O octa) had silver particles located on copper oxide particles in the same way as in Example 1; however, as the structure of the copper oxide particles was different from that of Example 1, the silver particles were uniformly dispersed on the copper oxide particles, and consequently, the Faraday efficiency for ethylene was lower than or similar to the Faraday efficiency for carbon monoxide, and the Faraday efficiency for hydrogen showed a tendency to increase to 15% or higher. Accordingly, it was confirmed that when silver (Ag) particles exist in an aggregated form on the surface of copper oxide particles, the selectivity for ethylene can be significantly improved.

[0107] (Experimental Example 2) Field Raman Analysis Experiment

[0108] When the catalysts of Example 1 (Ag / Cu2O cube), Comparative Example 3 (bare Cu2O cube), and Comparative Example 6 (Au / Cu2O cube) were each electrochemically converted to carbon dioxide using the method of Experimental Example 1, in situ Raman spectroscopic analysis was performed using a Raman spectrometer (XploRATM PLUS Raman spectrometer, HORIBA) equipped with a 785 nm laser and an immersion objective lens (Olympus, 60x). For each spectrum, the Raman signal collected for 102 seconds was corrected before acquiring the Si standard Raman spectrum, and the measurement results are shown in Fig. 5.

[0109] Specifically, FIGS. 5(a) to (c) show 200 to 700 cm of the catalyst according to Comparative Example 3, Comparative Example 6, and Example 1, respectively. -1 Raman spectra at, and FIGS. 5(d) to (f) are the 1800 to 2300 cm⁻¹ spectra of the catalysts according to Comparative Example 3, Comparative Example 6, and Example 1, respectively. -1 This is the Raman spectrum at, FIG. 5(g) is a graph showing the calculated HFB / (LFB+HFB) values ​​of the catalysts according to Example 1 (Ag / Cu2O cube), Comparative Example 3 (bare Cu2O cube), and Comparative Example 6 (Au / Cu2O cube), and FIG. 5(h) shows that in the catalysts of Example 1, Comparative Example 3, and Comparative Example 6, C 2+ Ratio of Faraday efficiency of compounds and C1 compounds (C 2+ This is a graph measuring / C1).

[0110] The Raman spectra of FIGS. 5(a) to (c) indicate the presence of *CO adsorbed on Cu. For Comparative Example 3 (bare Cu2O cube) and Comparative Example 6 (Au / Cu2O cube), 350 to 370 cm⁻¹ -1 and 520 to 530 cm -1In the results, only the Cu-CO stretching peak and the Cu-OH bond peak were detected, respectively; however, the catalyst of Example 1 (Ag / Cu2O cube) showed not only the Cu-CO stretching peak and the Cu-OH bond peak but also peaks from 270 to 280 cm⁻¹. -1 In addition, a Cu-CO rotation peak was detected, indicating that the catalyst of Example 1 is advantageous for CC dimerization because a large amount of *CO adsorbed on the Cu surface exists compared to the catalysts of Comparative Examples 3 and 6.

[0111] More specifically, referring to FIGS. 5(b) and (c), the catalyst of Example 1 had a higher surface adsorption rate (coverage) of *CO intermediates on the Cu surface than the catalyst of Comparative Example 6. That is, with the catalyst of Example 1, a large amount of carbon monoxide intermediates were generated from carbon dioxide by aggregated silver (Ag) particles, and as the carbon monoxide intermediates were effectively supplied to the surface of copper oxide particles, ethylene production through the dimerization of carbon monoxide intermediates occurred smoothly. On the other hand, although carbon dioxide was converted to carbon monoxide by gold (Au), the catalyst of Comparative Example 6 could not provide an effect of improving C2 compound selectivity due to the dimerization of carbon monoxide intermediates on the copper surface because the carbon monoxide intermediates were widely adsorbed across the entire gas diffusion electrode rather than on the Cu surface. Furthermore, since gold (Au) has a *CO binding energy approximately twice as high as silver (Ag), it is difficult to transport carbon monoxide generated on the gold (Au) surface to the surface of the copper particles. Furthermore, when copper oxide particles have a hexahedral structure, the distance between gold (Au) and copper oxide particles is greater compared to octahedral and hexaoctahedral structures, which limits the adsorption of carbon monoxide intermediates onto the copper surface.

[0112] As shown in FIGS. 5(d) to (f), CO stretching bands were investigated to confirm the behavior of *CO adsorbed on the copper surface. 2000 cm -1Below, bridge CO band, 2050~2060 cm -1 and 2080~2090 cm -1 CO stretching band peaks were observed for the low frequency band (LFB) and high frequency band (HFB), respectively. Compared to LFB CO and HFB CO, bridge CO has a higher energy barrier for CC dimerization; in particular, HFB CO exhibits excellent activity for CC dimerization, [regarding] C with two or more carbon atoms 2+ It has the advantage of being able to form compounds more easily. Compared to the catalysts of Comparative Examples 3 and 6, a narrow and strong peak for HFB CO was detected particularly in the catalyst of Example 1, C 2+ It can be seen that the selectivity for the compound can be increased.

[0113] Figure 5(g) is a graph showing the quantitative analysis of the intensity ratio of the HFB CO peak and the LFB CO peak. The catalyst of Example 1 exhibits the highest HFB / (LFB+HFB) value, allowing CC dimerization to be performed at a lower energy, thus C 2+ The selectivity of the compound was improved. However, the catalysts of Comparative Examples 3 and 6 exhibited significantly lower HFB / (LFB+HFB) values ​​compared to Example 1, indicating that not only did the energy required for CC dimerization increase, but C 2+ The selectivity for compounds also decreases, so C such as ethylene from carbon dioxide 2+ It was difficult to obtain the compound.

[0114] As shown in the graph of Fig. 5(h), among the carbon dioxide conversion products, the Faraday efficiency (C of compounds with 2 or more carbon atoms) of compounds having 2 or more carbon atoms 2+ The ratio of ) and the Faraday efficiency (C1) of compounds with 1 carbon atom (C 2+ When comparing / C1), the catalyst of Example 1 is C at -0.85 V. 2+ / C1 was 2.5, showing a value more than twice as high as Comparative Example 3 (1.1) and Comparative Example 6 (0.85). Accordingly, the carbon dioxide reduction catalyst of the present invention, in which silver (Ag) particles aggregated on the surface of polyhedral copper oxide particles are located, has C with 2 or more carbon atoms. 2+ It was confirmed that the selectivity for the compound can be significantly improved.

[0115] As described above, the present invention has been explained by specific details, limited embodiments, and drawings; however, this is provided merely to aid in a more comprehensive understanding of the invention, and the invention is not limited to the above embodiments. Those skilled in the art can make various modifications and variations from this description.

[0116] Accordingly, the scope of the present invention is not limited to the described embodiments, and all things equivalent to or having equivalent variations to the claims set forth below, as well as the claims set forth below, shall be considered to fall within the scope of the concept of the present invention.

Claims

Claim 1 A carbon dioxide reduction catalyst comprising: copper oxide particles having a polyhedral structure; and second silver (Ag) particles located on the surface of the copper oxide particles, wherein a plurality of first silver (Ag) particles are aggregated; wherein the copper oxide particles have a hexahedral structure, the second silver (Ag) particles are located on the (100) face of the copper oxide particles, and the copper oxide particles are a carbon dioxide reduction catalyst comprising Cu2O, wherein the carbon dioxide reduction catalyst converts carbon dioxide into a C2+ compound having two or more carbon atoms. Claim 2 delete Claim 3 A carbon dioxide reduction catalyst according to claim 1, wherein the ratio (D1 / D2) of the average particle size (D1) of the first silver (Ag) particle and the average particle size (D2) of the second silver (Ag) particle is 0.01 to 0.

5. Claim 4 delete Claim 5 In claim 1, the catalyst is a carbon dioxide reduction catalyst for the production of ethylene. Claim 6 A carbon dioxide reduction catalyst according to claim 1, wherein the size of the copper oxide particles is 500 to 1000 nm. Claim 7 delete Claim 8 (S1) a step of preparing copper oxide particles with a hexahedral structure by adding a reducing agent to a solution containing a copper precursor; and (S2) a step of adding a silver (Ag) precursor to the solution containing the copper oxide particles; wherein step (S2) involves performing a galvanic replacement reaction between the silver (Ag) precursor and the copper oxide on the surface of the copper oxide particles, and step (S2) involves the aggregation of silver (Ag) particles on the crystal plane (100) of the copper oxide particles with a hexahedral structure. A method for preparing a carbon dioxide reduction catalyst. Claim 9 delete Claim 10 delete Claim 11 delete Claim 12 A carbon dioxide conversion method comprising: a step of supplying carbon dioxide to a reactor comprising a carbon dioxide reduction catalyst according to any one of claims 1, 3, 5 and 6; and a step of discharging a product generated by reducing the carbon dioxide; wherein the carbon dioxide conversion method uses a continuous flow reactor. Claim 13 In paragraph 12, among the above products, a compound having 2 or more carbon atoms (C 2+ The ratio of ) and the Faraday efficiency of a compound with 1 carbon atom (C1) (C 2+ / C1) is 1.5 to 4.0, a carbon dioxide conversion method. Claim 14 In claim 12, the carbon dioxide conversion method wherein the product gas comprises ethylene. Claim 15 A carbon dioxide conversion method according to claim 12, wherein the continuous flow reactor comprises: a first electrode comprising a carbon dioxide conversion catalyst; a second electrode disposed opposite to the first electrode; and an electrolyte in contact with the first electrode and the second electrode, wherein the first electrode comprises a porous support having a carbon dioxide catalyst fixed thereon.